2005
DOI: 10.3168/jds.s0022-0302(05)73124-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre- and Postfresh Transition Diets Varying in Dietary Energy Density on Metabolic Status of Periparturient Dairy Cows

Abstract: Effects of dietary energy density during late gestation and early lactation on metabolic status of periparturient cows were studied. Four weeks before expected calving, animals were fed a low (DL; 1.58 Mcal of NEL/kg) or high energy density diet (DH; 1.70 Mcal of NEL/kg). After calving, half of the cows from each prepartum treatment were assigned to a low (L; 1.57 Mcal of NEL/kg) or high energy density diet (H; 1.63 Mcal of NEL/kg) until d 20 postpartum. After d 20, all animals were fed H until d 70. Animals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
48
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 34 publications
18
48
1
1
Order By: Relevance
“…The higher glucose and lower NEFA concentrations during the last 3 weeks of gestation (Table 2) in cows offered the H diet suggest that these cows were mobilising less body fat than cows offered diet L, which was attributable to the differences in energy intake. A similar effect has also been observed during the last few weeks of gestation in other experiments (Grum et al, 1996;Holtenius et al, 2003;Rabelo et al, 2005;Douglas et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The higher glucose and lower NEFA concentrations during the last 3 weeks of gestation (Table 2) in cows offered the H diet suggest that these cows were mobilising less body fat than cows offered diet L, which was attributable to the differences in energy intake. A similar effect has also been observed during the last few weeks of gestation in other experiments (Grum et al, 1996;Holtenius et al, 2003;Rabelo et al, 2005;Douglas et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
“…Offering a high-energy-density diet (H) in the dry period has, in some studies, increased non-esterified fatty acids (NEFA) post-calving, compared to a low-energy-density diet (L) (Rukkwamsuk et al, 1998;Holtenius et al, 2003), but most studies have found no effect (Minor et al, 1998;Tesfa et al, 1999;Holcomb et al, 2001;Doepel et al, 2002;Rabelo et al, 2005;Dann et al, 2006). Different results have also been reported for liver lipid/triacylglycerol (TAG) where one study has shown a decreased content post-calving for cows offered an H diet in the dry period compared to an L diet (Doepel et al, 2002), others the opposite (Rukkwamsuk et al, 1998;Douglas et al, 2006), whereas others again have found no effect (Grum et al, 1996;Tesfa et al, 1999;Rabelo et al, 2005). These discrepancies between studies are likely to be explained by a variety of factors, such as number of animals per treatment, time points for blood/liver sampling postcalving, inclusion/exclusion of cows with clinical/subclinical ketosis or other diseases, and last but not least, the differences obtained in body condition scores (BCS) at calving between cows offered an H or L diet.…”
Section: Introductionmentioning
confidence: 99%
“…No statistically significant differences were found for any traits or groups either before or after parturition. Rabelo et al (2005) reported a decline of pH values in a group with higher energy content in the FR, but no significant differences in the sums of VFA were found. All values of rumen fluid measured in our experiment are shown in Table 7.…”
Section: Average Values Of Rumen Fluid and Blood Serum Parametersmentioning
confidence: 99%
“…We [21,22] conducted an experiment to examine feeding strategies for transitioning cows from low-energy far-off dry cow diets to high-energy lactation diets. A 2 Ă— 2 factorial arrangement of treatments was used; cows were fed diets containing 1.55 or 1.65 Mcal NEl/kg DM for the last 4 wk prior to calving.…”
Section: Post-fresh Transition Cowsmentioning
confidence: 99%